Influence of vibrational non-equilibrium on the polarizability and refraction index in air: computational study. (20th December 2019) - Tropina, Albina A; Wu, Yue; Limbach, Christopher M; Miles, Richard B
Abstract: Knowledge of optical effects accompanying hypersonic flight conditions is of critical importance to ensure reliable operation of on-board optical instrumentation. This paper presents results of calculations of scalar polarizability dependence on vibrational non-equilibrium in molecular nitrogen and oxygen. The non-equilibrium effects are evaluated on the basis of a semi-classical model for the molecular polarizability. It is shown that, depending on the vibrational and translational populations, changes in the scalar polarizability in excess of normal density and temperature scaling can be around 1%–5% at moderate gas temperatures and around 10% at high temperatures. The model was applied to predict the polarizability for non-equilibrium states in a nitrogen plasma formed by a single nanosecond pulse with different rise times.